Sawan: exploring the knowledge and wisdom of Javanese traditional healing practices - Suyami Suyami; Fakhriati Fakhriati; Ninawati Syahrul; Devi Fauziyah Ma’rifat; Sumarno Sumarno; Yustina Hastrini Nurwanti; Titi Mumfangati; Mirna Yusuf; Pantaria Noor Fitri Hapsari; Triyasinta Noor Laksmita Dewi (Cogent Arts & Humanities)
In the current digital era, despite technological advancements and increased access to education, there remains a significant population in Indonesia that believes in traditional healing practices associated with ‘mystical’ illnesses. One such illness is sawan. This research aims to provide a comprehensive description of the forms, factors, as well as treatments or prevention of sawan through qualitative research and case studies. Data was collected through participant observation and in-depth interviews with 40 informants from various regions in Java. The findings reveal five types of sawan: sawan mayit, sawan bayi, sawan manten, sawan sambaing dalan, and sawan candhikala/sawan celeng. Additionally, the data also uncovered that sawan, along with preventive and curative measures available, include the use of mantras and traditional herbal remedies known as singgul. This research provides insights into alternative healing in the health field and serves as a foundation for further research on this subject, including studies beyond the island of Java and the exploration of the origins of sawan terminology.